CARLOS LUIS FALLAS: DIFUSIÓN, COMERCIALIZACIÓN Y ESTUDIO DE SUS OBRAS. UNA CONTRIBUCIÓN DOCUMENTAL - Molina Jiménez, Iván (Universidad de Costa Rica, 2012)
This article analyzes the distribution, marketing and study of the books of the Costa Rican Communist writer, Carlos Luis Fallas Sibaja (1909-1966). The main sources for this research are two annexes: the first, compiles bibliographic data on his novels and short stories and the second, the scholarly works referred to such books. The article also includes a detailed chronology that retrieves the basic facts of the political and literary life of Fallas.